First-line immune checkpoint inhibitors with chemotherapy in advanced gastric and gastroesophageal junction adenocarcinoma: a meta-analysis of phase 3 trials - Lin, Yuxuan; Liao, Yonghe; Shen, Jinhai (Frontiers in Immunology, 2025)
BackgroundThe integration of immune checkpoint inhibitors (ICIs) with chemotherapy (CT) regimens has become a critical focus of clinical investigation in the management of advanced gastric and gastroesophageal junction (G/GEJ) adenocarcinoma over the past several years. Recent phase 3 trials have yielded diverse outcomes, sparking significant debate within the oncological community. In response to these disparate findings, we conducted a meta-analysis to evaluate the therapeutic efficacy and safety profile of this strategy.MethodsA literature search on PubMed and in major conference proceedings was carried out through December 15, 2024. For efficacy, summary hazard ratios (HRs) for progression-free survival (PFS) and overall survival (OS), odds ratios (ORs) for the objective response rate (ORR) were calculated; for safety, relative risks (RRs) for adverse events (AEs) were assessed.ResultsNine phase 3 clinical trials, including KEYNOTE-062, CheckMate 649, ATTRACTION-4, ORIENT-16, GEMSTONE-303, KEYNOTE-811, KEYNOTE-859, RATIONALE-305, and COMPASSION-15, which involved a total of 7,825 patients, were analyzed. The addition of ICIs to CT was associated with better PFS (HR, 0.71; 95% CI, 0.65-0.79), OS (HR, 0.79; 95% CI, 0.75-0.83), and a higher ORR (OR, 1.57; 95% CI, 1.43-1.72) compared with CT standalone treatment. However, this combination therapy increased the risk of grade 3–5 AEs (RR, 1.15; 95% CI, 1.09-1.22) and serious AEs (RR, 1.44; 95% CI, 1.21-1.70).ConclusionFor patients with advanced G/GEJ adenocarcinoma, the addition of ICIs to CT regimens as a first-line treatment offers superior efficacy compared to CT alone, though it comes with an increased risk of toxicity. In the context where multiple strategies are accessible, the pharmacological safety profile can guide practitioners in identifying the most suitable intervention for patients with a higher likelihood of deriving benefits from specific treatment strategies.